Phenomenological study of decline of personal health records: Empirical evidence from thematic analyses of blogs' content - Ravi Chinta; Vijay V. Raghavan (Cogent Business & Management, 2015)
This study examines the current state of personal health records (PHRs) in electronic health care. Surveys report that the PHR usage is generally increasing, and yet, even an influential organization such as the Google decided to end its “Google Health” venture. If the potential for use and future growth is high, why are there so many obstacles to the adoption of PHRs? We analyze comments to articles and blogs related to PHRs in order to identify the current status, barriers to adoption, and future potential of PHRs. This study identifies issues of PHRs clustering mainly around certain key ideas: trust, communication, markets, standards, usability, politics, usefulness, and data ownership. It appears that disparity among the multiple stakeholders as to the expected benefits is the main barrier to its adoption.
Keywords: 650